Cation distribution and magnetic analysis of wideband microwave absorptive CoxNi1−xFe2O4 ferrites. Issue 9 (15th June 2017) - Torkian, Shahab; Ghasemi, Ali; Shoja Razavi, Reza
Abstract: Cox Ni1−x Fe2 O4 ferrites (x=0, 0.2, 0.4, 0.4, 0.6, 0.8 and 1) were prepared by a sol-gel auto-combustion method. The samples were structurally characterized by X-ray diffractometry (XRD), field emission scanning electron microscopy (FE-SEM), energy dispersive X-ray analysis (EDX), and Fourier transform infrared spectroscopy (FTIR). The XRD patterns confirmed single phase formation of spinel structure. Cation distribution estimated from XRD data suggested the mixed spinel structure of ferrite. The EDX analysis was in good agreement with the nominal composition. The results of FTIR analysis indicated that the functional groups of Co-Ni spinel ferrite were formed during the combustion process. According to FE-SEM micrographs, by addition of cobalt ion the average particle size of substituted nickel ferrite was gradually became smaller from 450 nm to 280 nm. Magnetic measurement using vibrating sample magnetometer (VSM) showed an increase in saturation magnetization and coercivity by Co 2+ substitution in nickel ferrite. For Co0.8 Ni0.2 Fe2 O4 sample, M s and H c reaches as high as 93 emu/g and 420 Oe, respectively. The reflection loss properties of the nanocomposites were investigated in the frequency range of 8–12 GHz, using vector network analyzer (VNA). Cobalt substitution could enhance reflection loss of NiFe2 O4 ferrite. The maximum reflection loss value of the Co 2+ substituted Ni ferrite was ~ −26 dB (i.e. over 99% absorption) at 9.7 GHz with bandwidth of 4 GHz (RL<– 10 dB) through the entire frequency range of X-band.